Założenia restrukturyzacji naprawczej i rozwojowej - Jarka, Sławomir (Assumptions for Improvement and Development Restructuring, 2005)
The paper presents the typology of restructuring processes that were planned and accomplished in these firms which had been set up with the assets of state agricultural farms (PGR), overtaken by government to Agricultural Property Stock of the State Treasury. This process was realized in enterprises with good financial situation as well as in firms which lost or were threatened to lose financial fluency and credit ability. According to that, there are two types of restructuring: improvement and development. They often appear in a firm at the same time and there are no explicit borders between them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 348-351